Pepper mild mottle virus as an indicator of fecal pollution - Rosario, Karyna; Symonds, Erin M; Sinigalliano, Christopher; Stewart, Jill; Breitbart, Mya (Applied and environmental microbiology, 2009)
Accurate indicators of fecal pollution are needed in order to minimize public health risks associated with wastewater contamination in recreational waters. However, the bacterial indicators currently used for monitoring water quality do not correlate with the presence of pathogens. Here we demonstrate that the plant pathogen Pepper mild mottle virus (PMMoV) is widespread and abundant in wastewater from the United States, suggesting the utility of this virus as an indicator of human fecal pollution. Quantitative PCR was used to determine the abundance of PMMoV in raw sewage, treated wastewater, seawater exposed to wastewater, and fecal samples and/or intestinal homogenates from a wide variety of animals. PMMoV was present in all wastewater samples at concentrations greater than 1 million copies per milliliter of raw sewage. Despite the ubiquity of PMMoV in human feces, this virus was not detected in the majority of animal fecal samples tested, with the exception of chicken and seagull samples. PMMoV was detected in four out of six seawater samples collected near point sources of secondary treated wastewater off southeastern Florida, where it co-occurred with several other pathogens and indicators of fecal pollution. Since PMMoV was not found in nonpolluted seawater samples and could be detected in surface seawater for approximately 1 week after its initial introduction, the presence of PMMoV in the marine environment reflects a recent contamination event. Together, these data demonstrate that PMMoV is a promising new indicator of fecal pollution in coastal environments.